Innovation to the core : a blueprint for transforming the way your company innovates - Skarzynski, Peter. (Harvard Business School Press, 2008)
Building on the work of strategy guru Gary Hamel, this guide shows organizations how to move innovation from a buzz word to a core competency. Skarzynski, a consultant on international growth and strategy, and Gibson, a global business strategist, draw on a wealth of examples from real companies including GE, Procter & Gamble, Nokia, and IBM. They provide frameworks, step-by-step action lists, and other practical tools for improving an organization's capacity for innovation by mobilizing the imagination of employees, customers, and business partners.